Overall Instability Failure Mechanism and Monitoring Strategy Research of the Shallow Tunnel under Unsymmetrical Pressure during Operation Period - Hongyan Guo; Xinrong Liu; Ke Li; Zuliang Zhong (Advances in Materials Science and Engineering)
Aiming at the safety of tunnel operation, based on the investigation and statistical analysis of a large number of operating tunnel diseases, comprehensively considering the interaction between the surrounding rock and the structure, this paper establishes the failure criteria for surrounding rocks and lining materials by using numerical limit analysis and theoretical analysis methods, analyzes the overall stability and instability failure mechanism on the shallow tunnel under unsymmetrical pressure during the operation period by using the strength reduction method in light of the operation safety of the tunnel, proposes the reasonable monitoring strategy, and also constructs monitoring index system. The analysis and research results show that the tunnel structure is affected by bias pressure due to the asymmetry of the terrain. The probability of disease in the bias pressure tunnel under asymmetric terrain conditions is significantly higher than that of the general terrain. The shallow tunnel under unsymmetrical pressure has experienced three development stages from shear failure to overall instability, including rock mass fracture and sliding, structural damage, and overall instability, which can be divided into eight processes. During operation, the key monitoring indicators of surface deformation are the subsidence and deformation of the slope top and the horizontal displacement of the slope itself, followed by the monitoring of the uplift and deformation at the bottom of the slope. Meanwhile, close attention should be paid to the structural stress states in the sliding direction and perpendicular to the sliding direction of the lining structure, which demonstrates that the principal compressive stress in the sliding direction is more sensitive than the principal tensile stress in perpendicular to the sliding direction and should be listed as the key monitoring and early warning indicators of the structural stress.